2020
DOI: 10.21037/tgh.2020.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse gastric cancer: histologic, molecular, and genetic basis of disease

Abstract: Gastric cancer (GC) is the fifth most common malignancy with over 1,000,000 cases diagnosed annually and is the third leading cause of cancer death globally (1). The incidence is highest in Asia (with over half of all GC cases globally diagnosed in East Asia), Eastern Europe, and South America with comparatively lower rates in Africa, North America, and Europe. Approximately 95% of gastric tumors are gastric adenocarcinomas (GAC) which can be further divided into intestinal type gastric cancer (IGC), diffuse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…PFS and OS medians for the series of 7.7 months (95% CI 7.3-8.0) and 13.9 months (12.9-14.7), respectively, are conditioned by the exclusion of Lauren diffuse-type adenocarcinomas, which are specific to gastric cancer and are associated with worse prognosis, as well as responding differently to chemotherapy. Given that diffuse adenocarcinoma is a different entity, it has not been factored into this analysis [15,19,20,24]. Likewise, the exclusion of diffuse subtype cancers determines a high percentage of HER2+ neoplasms in this series: 45%, 33.5%, and 30.1% in GEJ-AC, EAC, and GAC, respectively, versus 15-20% in most reported studies that fail to differentiate by Lauren subtype [15,25].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…PFS and OS medians for the series of 7.7 months (95% CI 7.3-8.0) and 13.9 months (12.9-14.7), respectively, are conditioned by the exclusion of Lauren diffuse-type adenocarcinomas, which are specific to gastric cancer and are associated with worse prognosis, as well as responding differently to chemotherapy. Given that diffuse adenocarcinoma is a different entity, it has not been factored into this analysis [15,19,20,24]. Likewise, the exclusion of diffuse subtype cancers determines a high percentage of HER2+ neoplasms in this series: 45%, 33.5%, and 30.1% in GEJ-AC, EAC, and GAC, respectively, versus 15-20% in most reported studies that fail to differentiate by Lauren subtype [15,25].…”
Section: Discussionmentioning
confidence: 95%
“…The (TCGA) The Cancer Genome Atlas Research Network classification system, has recognized molecular features of EAC, which closely resemble those of chromosomal instable (CIN) gastric cancer, albeit with a gradient of molecular alterations throughout the upper gastrointestinal tract with as yet unknown clinical correlation and treatment implications [14][15][16][17][18]. Furthermore, Lauren's diffuse subtype esophagogastric adenocarcinoma displays specific clinical, histopathological, molecular, and therapeutic characteristics, regardless of having been traditionally included indistinctly with intestinal-type adenocarcinoma [15,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies demonstrated that the maximum SUVs of gastric cancers with signet ring cell carcinoma histopathology and diffuse types of Lauren classification were significantly lower than those of papillary/tubular adenocarcinoma and intestinal type, respectively [ 28 , 29 , 30 ]. This finding is considered to result from the distinct histopathological features of signet ring cell carcinoma and diffuse-type gastric cancer, which have a relatively small number of cancer cells with scattered distributions and rich fibrous stroma [ 30 , 31 ]. Furthermore, the distinct molecular and metabolic features of signet ring cell carcinoma, such as low expression levels of glucose transporter-1 and pyruvate kinase, also contribute to low FDG uptake [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary stomach cancer is associated with mutations in the CDH1 gene and it is also manifested in Lynch (hereditary nonpolyposis colorectal cancer) syndrome related to mutations in mismatch repair genes [45][46][47][48]. Next-generation sequencing studies have identified rare germline variants in several other genes, including BRCA2 and other DNA repair genes [49][50][51]. In kidney cancer, the contribution of von Hippel-Lindau syndrome is a likely explanation for the early onset risk component [52].…”
Section: Genetic Implicationsmentioning
confidence: 99%